Misleading guidelines for the diagnosis and management of hypertension - Flávio Danni Fuchs (Clinical and Biomedical Research, 2014)
International guidelines for the diagnosis and management of hypertension were recently released [1,2]. A historical trend of lowering the blood pressure (BP) thresholds to diagnose hypertension in high risk individuals was unexpectedly reversed. BP targets for the treatment were modified accordingly. Therefore some individuals who were hypertensive before are now normotensive. Other guidelines still recommend the previous diagnostic limits and goals of treatment [3-5], resulting that an individual may be hypertensive in some countries and normotensive in others. The guidelines are more homogeneous in the recommendations for treatment, particularly in regard to the liberal options of drugs to starting the treatment. Unfortunately, in my view, this liberal view includes drugs without unbiased evidences of effectiveness, such as Angiotensin Receptor Blockers (ARB). In this point of view, I discuss the reasons and misconceptions in the establishment of diagnostic thresholds and the shortcomings in the recommendations of antihypertensive drugs.